Measurement of Customer Perceptions of Logistics Service Quality - Babatunde Enitan Ogunnowo; Salami Suberu Sule (Department Industrial Engineering, University of Muhammadiyah Malang, 2021)
Currently, logistics service providers experience a high increase in activity. It makes logistics service providers compete with each other in service quality. To be able to compete, logistics service providers need to measure customer perceptions on logistics service satisfaction. The results of measuring customer perceptions can be used to improve the quality of logistics services. This study attempted to measure customer perceptions of third-party logistics (3PL) service users by considering competitor performance factors. This study integrated the Customer Satisfaction Index (CSI) method and the Competitive Zone of Tolerance based Importance Performance Analysis (CZIPA) method to measure customer perceptions and determine the priority attributes for improvement account competitors' performance factors. Based on the research, the CSI method was proven to measure customer perceptions of 3PL service users. CZIPA can determine the attributes that were prioritized for improvement based on the performance of competitors.